Anaplasma Infection in Ticks, Livestock and Human in Ghaemshahr, Mazandaran Province, Iran. - Nasibeh Hosseini-Vasoukolaei; Mohammad Ali Oshaghi; Parviz Shayan; Hassan Vatandoost; Farhang Babamahmoudi; Mohammad Reza Yaghoobi-Ershadi; Zakkyeh Telmadarraiy; Fatemeh Mohtarami (Tehran University of Medical Sciences, 2014)
Background: Anaplasmosis is an important issue for animal breeders in terms of economic losses as well as a health concern to human. Ticks are considered as the main vector of this disease. Lack of documented information about Anaplasma species in Iran was the scope of this study to determine the population of ticks and the presence of Anaplasma in ticks, domestic ruminants and also human beings in northern Iran. Methods: A total of 101 unengorged hard ticks, 78 domestic ruminants and 40 human blood samples collected from Ghaemshahr, Mazandaran Province, northern Iran were tested by nested PCR against 16s rRNA gene of  Anaplasma species. Results: Positive PCR was found in 50 ticks, 28 sheep, 2 cattle, one goat, and 10 human specimens. Sequence analy- sis of the PCR products confirmed presence of A. ovis in two Rhipicephalus sanguineus and two Ixodes ricinus ticks, one human and 4 sheep samples. Moreover one Boophilus annulatus tick and one sheep sample were infected with A. bovis. Furthermore one sample of sheep was infected with A. centrale. Conclusion: This study is the first report of tick infection to A. ovis, A. bovis and human infection to A. ovis in Iran. The result of this study is a survey of Anaplasma infections from ticks, domestic animals and human in Iran which help to have appropriate prevention measures for anaplasmosis.